3 - Les Figures Sociales de la Participation Associative dans la Cooperative des Planteurs d’Hevea de Songon (Cote – d’Ivoire) - Sedji Donald Akre (African Sociological Review, 2019)
Qualitative in nature, this article presents the results of a study carried out in 2008 and updated in 2014 in the town of Songon with twenty – five (25) actors. Based on the concept of solidarity within associations or community organizations, this text highlights the forms and challenges of participation and membership in community organizations, particularly within a cooperative enterprise called: Coopérative des Planteurs d’Hévéa de Songon (Cophes) in the District of Abidjan .Thus, starting from the experience of the establishment of the functioning of social loans within this social entity, this article shows how, in the “name” of solidarity, members of this organization have developed forms of social responses to this operation through the non– repayment and / or problems of repayment of said loans. Indeed, leaning on the ideological aspects of cooperation and forms of collective mobilization, such as the ideology of “family” and “gift” these actors have reworked and shaped the “associative participation” perceptible at the structural level . In this respect, this cooperative experience offers an interesting material for re – reading the notion of “participation”: what we call here the social figures of associative participation. Seen from this angle, this form of participation provides information on the representations of these actors with regard to the cooperative phenomenon.